2012
DOI: 10.1128/jvi.00369-12
|View full text |Cite
|
Sign up to set email alerts
|

Naturally Occurring Swine Influenza A Virus PB1-F2 Phenotypes That Contribute to Superinfection with Gram-Positive Respiratory Pathogens

Abstract: A combination of viral, bacterial, and host factors contributes to the severity and overall mortality associated with influenza virus-bacterium superinfections. To date, the virulence associated with the recently identified influenza virus protein PB1-F2 has been largely defined using models of primary influenza virus infection, with only limited assessment in models of Streptococcus pneumoniae superinfection. Specifically, these studies have incorporated isogenic viruses that differ in the PB1-F2 expressed, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
53
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(60 citation statements)
references
References 59 publications
6
53
1
Order By: Relevance
“…Similarly, infection of mice with IAV expressing PB1-F2 was reported to significantly enhance the predisposition to secondary bacterial infections (25,26). We observed no effect of PB1-F2, either amorphous or amyloidal, on E. coli growth and only an ephemeral inhibitory effect on B. subtilis growth.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Similarly, infection of mice with IAV expressing PB1-F2 was reported to significantly enhance the predisposition to secondary bacterial infections (25,26). We observed no effect of PB1-F2, either amorphous or amyloidal, on E. coli growth and only an ephemeral inhibitory effect on B. subtilis growth.…”
Section: Discussionsupporting
confidence: 55%
“…Likewise, PB1-F2 can disturb the inner membrane of mitochondria, which induces apoptosis. Other functions of PB1-F2 have been also reported: PB1-F2 co-localizes in the nucleus of infected epithelial cells and up-regulates viral polymerase activity (19,20); PB1-F2 may be implicated in inflammation and can modify the host pro-inflammatory response induced by IAV infection (11,21,22); PB1-F2 may inhibit the IFN pathway induction through interacting with the mitochondrial antiviral signaling protein, MAVS (23,24); PB1-F2 was also shown to enhance the predisposition to secondary bacterial infection (11,25,26).…”
mentioning
confidence: 99%
“…That said, we were surprised by our findings in NHPs, because numerous studies using rodent models have demonstrated that antecedent IAV infection causes a significant increase in morbidity and mortality following secondary S. aureus respiratory tract infection. [26][27][28][29] There are several possible explanations for the noted differences.…”
Section: Discussionmentioning
confidence: 98%
“…Several possible mechanisms have been suggested, including mitochondrial targeting and proapoptotic activity (8,9,19), enhancing PB1 function (20), and inhibition (21)(22)(23)(24)(25)(26)(27) or enhancement (28) of the IFN-␤ response. PB1-F2 has also been linked to bacterial infections following IAV infection (29)(30)(31)(32). However, most of these phenotypes have been difficult to generalize to all strains of virus and across host models tested.…”
mentioning
confidence: 99%